Distribución espacial del potencial íctico y ornitológico en la parte baja del rio Mayo 2008. - Bartra Valles, Richard Harry (2009)
This research "special document fish and bird distribution potential of the lower basin of the river Mayo. 2008 ", aimed to determine how these groups of organisms along the main channel, based on the current lack of information and the need to generate management tools for their sustainable use is distributed. For the ornithological sampling kilometer abundance index, with observation and direct recording on both banks of the river in May was used. GPS instruments such as binoculars, cameras and inflatable boat, which made possible the slightest disturbance in data collection were used. The ichthyological sampling was day and night in the first of this was done in a timely manner with the help of Tarrafa, while in the second case was carried through the trawl nets aboard rubber bladder. In both cases preferential systematic sampling was applied. 2727 individuals of birds in 18 orders and 38 families were I recorded, according to the specific richness diversity indices as Shannon analyzed - Wiever (H ') where the sector I was the most diverse (H' = 3.6), followed by Sector II (H '= 3.3) and finally the Sector II, which presented the lowest diversity (H' = 3.2), compared to 744 ichthyological sampling fish species being the most abundant Pterygoplichty sp "Carachama" were recorded. It is considered that the spatial distribution of the two groups of vertebrates evaluated directly related to human activities, physiographic features and conditions of riparian vegetation